Dampak Fluktuasi Dinamis Makro Ekonomi, IHSG, dan SIBOR Terhadap Jakarta Islamic Index - Ris Yuwono Y. Nugroho (InFestasi, 2011)
Capital markets can be a leading indicator for the economy. Shariah Index has taken  place in the process of  Islamization of capital markets at once is Islamic capital market development. The purpose of this study to (1) know the description of the dynamics of JII, JCI, Index of Industrial Production, and SIBOR, (2) evaluate the response to shocks Jakarta  Islamic Index  stock index, the Index of Industrial Production, and SIBOR.  Analysis using Vector Autoregression. VAR is built  with consideration to minimize the theoretical approach capable of capturing  economic  phenomena. Description  JII and  JCI  showed  a similar  pattern, the Index of Industrial  Production has an increasing trend,  while  SIBOR fluctuates  and  tends to fall.  Shocks that  occurred in the JII, JCI  and the Index of Industrial  Production  will be responded  positively by JII, while the shocks that occurred in SIBOR will respond in the opposite direction.